2016
DOI: 10.1111/twec.12412
|View full text |Cite
|
Sign up to set email alerts
|

How Do Exporters React to Changes in Cost Competitiveness?

Abstract: Various international institutions such as the European Commission, the ECB and the OECD often use unit labour costs as a measure of international competitiveness. The goal of this paper was to examine how well this measure is related to international export performance at the firm level. To this end, we use Belgian firm‐level data for the period 1999 to 2010 to analyse the impact of unit labour costs on exports. We find an estimated elasticity of the intensive margin of exports with respect to unit labour cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Finally, while this paper focuses on the short-to medium-run relationships between competitiveness and the macroeconomy, future research can shed light on the long-run effects of competitiveness shocks and investigate whether these long-run effects are heterogeneous across countries. 9 Using microeconomic data, Decramer, Fuss, and Konings (2016) find that exporters across sectors react very differently to reductions in unit labour costs, suggesting that national industry structures may help explain the heterogeneity found in this paper.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, while this paper focuses on the short-to medium-run relationships between competitiveness and the macroeconomy, future research can shed light on the long-run effects of competitiveness shocks and investigate whether these long-run effects are heterogeneous across countries. 9 Using microeconomic data, Decramer, Fuss, and Konings (2016) find that exporters across sectors react very differently to reductions in unit labour costs, suggesting that national industry structures may help explain the heterogeneity found in this paper.…”
Section: Discussionmentioning
confidence: 76%
“…The importance of non-price competitiveness is not restricted to Germany, however. Decramer, Fuss, and Konings (2014) found only a small negative effect of ULC on the export performance of Belgian firms with an estimated elasticity of the intensive margin of exports ranging between 595 -0.2 and -0.4, suggesting that pass-through of costs onto prices is limited and/or that demand for exported products is almost price-inelastic. Table 9 shows the European Commission's (2014)…”
Section: Q22mentioning
confidence: 93%
“…The importance of non-price competitiveness is not restricted to Germany, however. Decramer et al ( 2014 ) found only a small negative effect of ULC on the export performance of Belgian fi rms with an estimated elasticity of the intensive margin of exports ranging between −0.2 and −0.4, suggesting that pass-through of costs onto prices is limited and/or that demand for exported products is relatively inelastic. Table 4.3 shows the EC's recent estimations of the elasticity of export demand of several CMEs to the REER and foreign demand: exports of CMEs tend to have signifi cantly lower elasticity to REER changes and higher elasticity to foreign demand than exports of MMEs (whose elasticities are shown in Table 5.3 ).…”
Section: Trade Structures Skill Regimes and Non-price Competitivenessmentioning
confidence: 94%